Intergenerational Transmission of Spousal Inequality - Nguyen, Kieu-Dung (Estudios de Economía, 2021)
This paper studies whether sons and daughters reproduce in their relationships the same intra-household inequalities observed for their parents in terms of some economic statuses (wages, income, work hours, and education). Additionally, we emphasize the relevance of transmission of preference and gender-role attitude in investigating household issues. Utilizing the Panel Study of Income Dynamics’ data we find that married sons imitate their parents’ household disparities more than married daughters. For parents and their daughter’s family, the similarity in household inequalities is insignificant. The paper also examines the differential patterns of the statuses and the dynamics of educational gap patterns across generations.